Congenital transmission of Trypanosoma cruzi: An operational outline for detecting and treating infected infants in northwestern Argentina - Blanco, Sonia B. (2000)
We designed a set of procedures for first-line local health services to detect and treat the congenital transmission of Trypanosoma cruzi at a province-wide scale, and field-tested the programme in the province of Tucumam, northwestern Argentina, from 1992 to 1994. The programme consists of routine screening of pregnant women for seroreactivity to T. cruzi, serological and parasitological follow-up of the newborn at least twice during the first year of age, treatment of the infected infants, and evaluation of the outcome. 927 (5.5%) of 16 842 pregnant women were seroreactive to T. cruzi by indirect haemagglutination assay and ELISA. Twenty-one (6.7%) of 315 newborns to seroreactive mothers were diagnosed as infected with T. cruzi parasites microhaematocrit concentration before 30 days of age. Five newborns who initially tested negative had a T. cruzi infection detected by microhaematocrit and/or serological techniques at 3 or 6 months of age. Thus, congenital infection was diagnosed in 26 (7.1%) infants born to seroreactive women and residing in houses free of triatomine bugs. Four of 6 infants born to seroreactive mothers died during the first year of age and had some evidence of T. cruzi infection; one of the deaths was attributed to T. cruzi based on clinical evidence. After specific treatment with nifurtimox or benznidazole, 30 of 32 infants remained parasitologically and serologically negative. This study shows the feasibility of controlling the incidence of congenitally acquired T. cruzi infections at a province-wide scale by means of a specific screening programme at first-line health services level.